Computer aided support for the temperature control in buildings. (2017) - Zupančič, Borut
The paper briefly describes the Modelica model of a cubic shaped room with one window. The 'physical' model was then implemented as a Modelica (Dymola) block in MATLAB-Simulink environment. Simulink was used for the realisation of different control schemes, which were 'manually' and 'automatically' optimised. The experiments show that the synergetic combination of MATLAB-Simulink and Dymola-Modelica environments is an efficient and powerful approach giving the possibility to realise several important goals: realisation preserving modelling in Modelica, efficient simulation with Simulink and many possibilities for control system design and optimisation using basic MATLAB and appropriate MATLAB toolboxes. However the experiences with Modelica modelling taught us that Modelica models become rather complex and therefore model reduction techniques in order to obtain usable and efficient models are desired. The last part of the paper briefly describes some research activities in this area and also our contributions.